Transformative Leadership: Harnessing Religious Values for Positive Educational Outcomes - Wakhida Nurhayati; Zawirrahmi Zawirrahmi; Otisia Arinindyah; Nurhidayah Nurhidayah; Imam Asrofi; Masduki Asbari (Universitas Muhammadiyah Enrekang, 2024)
This research explores future educational leadership models with a focus on communication and human relations based on religious, philosophical, psychological, and sociological approaches. Using descriptive qualitative methods, data were collected through observation and in-depth interviews in several schools in Tangerang. The results showed that educational leaders who integrate spiritual values and ethical principles in their leadership practices are able to create a positive learning environment and support students' character development. Open and inclusive communication between leaders, staff and students contributes to improved motivation and performance. In addition, a deep understanding of psychological and sociological aspects assisted leaders in building healthy interpersonal relationships and creating fair policies. This study recommends the importance of continuous professional training for educational leaders to implement leadership models that are holistic and responsive to complex social dynamics. The findings are expected to contribute to the development of more effective and relevant educational leadership practices in the future.